Comparison of pelvic C-clamp and pelvic binder for emergency stabilization and bleeding control in type-C pelvic ring fractures - Audretsch, Christof K. (Sci Rep, 2021)
Severe bleeding is the major cause of death in unstable pelvic ring fractures. Therefore, a quick and efficient emergency stabilization and bleeding control is inevitable. C-clamp and pelvic binder are efficient tools for temporary bleeding control, especially from the posterior pelvic ring. Yet the C-clamp requires more user knowledge, training and equipment. However, whether this makes up for a more efficient bleeding control, is still under debate. Patients with a type-C pelvic ring fracture were identified from the German Pelvic Registry (GPR) and divided into three groups of 40 patients (1. no emergency stabilization, 2. pelvic binder, 3. C-clamp). The matching occurred according to the parameters age, gender, initial RR and initial HB. Complication—and mortality rates were compared especially regarding bleeding control. Regarding ISS and fracture dislocation there was no difference. The use of the C-clamp resulted in more complications, a higher mortality rate due to severe bleeding and more blood transfusions were admitted. Moreover the pelvic binder was established noticeably faster. However, the C-clamp was more often rated as effective. There is no evidence of advantage comparing the C-clamp to the pelvic binder, regarding bleeding control in type-C pelvic ring fractures. In fact, using the pelvic binder even showed better results, as the time until established bleeding control was significantly shorter. Therefore, the pelvic binder should be the first choice. The C-clamp should remain a measure for selected cases only, if an adequate bleeding control cannot be achieved by the pelvic binder.